Study the Scientific Productions of the Faculty Members of Traditional Medicine at Universities of Medical Science in Iran Medical in the Scopus Citation Database (2005-2015) - M Kazerani; M Bagheri Ghahfarrokhi; M Shekofteh (Institue of Medicinal Plants, ACECR, 2019)
Background: One of the most important aspects of research is the evaluation of scientific production, and this is important in traditional medicine due to its specific application in the treatment of diseases today. Objective: The purpose of this study was to analyze the scientific products of faculty members of Traditional Medicine in Iranian Medical Sciences Universities indexed in Scopus Citation Database between 2005 and 2015. Methods: This study is a descriptive survey with scientometric approach. Required data were extracted from Scopus Citation Database by September 21, 2015 and descriptive statistics were used to analyze the data. Results: Scientific production of the faculty members of the traditional medicine had a sustained upward trend, Tehran University has been known as the best in production (95 certificates) and the best in citation (369 citations).Iranian Journal of Public Health and Iranian Red Crescent Medical Journal have both published the largest scientific publications of the faculty members of traditional medicine in the country (each 16 certificates). Articles of journals (58.4%) and books (15.4%) were the most used sources by traditional faculty members. 8 magazines were selected as the core journals in the field of traditional medicine; the Journal of Ethnopharmacology was the first journal in this field. The maximum rate of citations is related to the references since 2007 to 2015. Conclusion: Access of researchers to core journals in the field of traditional medicine through valid databases, increase the research budgets, apply incentive programs, facilitation for sabbatical leaves, and the provision of research laboratories are some ways to Improve the quality and quantity of scientific production in this field.